PENGARUH TINDAKAN SUPERVISI TERHADAP TURNOVER INTENTION AUDITOR DENGAN BURNOUT DAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Adhisti, Maria Immaculata; Setyohadi, J. Sabas; S.P, J. Adithya (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The objective of this research is to empirically analyze the influence of Supervisory Actions on the Burnout, Job Satisfaction and Auditor’s Turnover Intention. The population of this research are external auditor’s who worked on Public Accountant Firms in province of DKI Jakarta. Sampling was conducted using a convinience sampling through questionare method. The data are analyzed by using path analysis with partial least square method of structural equation modeling (PLS-SEM). The result of direct effect to showed that the Supervisory Actions have a negative impact on the Burnout and Turnover Intention, while of the Supervisory Actions have a positive impact on the Job Satisfaction. And also then of direct effect to showed that the Burnout have a positive impact on the Turnover Intention, also that Burnout have a negative impact on the Job Satisfaction, and while of the Job Satisfaction have a negative impact on the Turnover Intention. The result also showed that the Burnout as a partial pararel mediation on the relationship between Supervisory Actions with Turnover Intention, and The Burnout as a partial pararel mediation on the relationship between Supervisory Actions with Job Satisfaction. And also of The Job Satisfaction as a partial pararel mediation on the relationship between Supervisory Actions with Turnover Intention. The result also showed that the Burnout and Job Satisfaction as a partial serial mediation on the relationship between Supervisory Actions with Turnover Intention